Between Hashtagging and Hashtrending: Counterculture, Dissent and Aesthetic Politics - Van Heerden, Chantelle Gray (Forum (Edinburgh), 2018)
The year 2016 was marked by a number of major events, some fleeting, others still ongoing, but almost all underscoring the need for thinking about a very different way of being in the world; in other words, producing radically different kinds of subjectivity. These events – which included Brexit and the election of real estate mogul and reality TV celebrity, Donald Trump, as the president of the U.S. – can be seen as part of the ongoing rise of right-wing populism that has marked world politics for at least the past decade. The continuing European migrant and refugee crises, too, have been harnessed by politicians to create voter fear around personal security in terms of jobs and safety, and national security in terms of terrorism. Accordingly, these kinds of political strategies create a victim-perpetrator binary.